Enhanced chondrogenic differentiation of human mesenchymal stems cells on citric acid-modified chitosan hydrogel for tracheal cartilage regeneration applications. Issue 30 (8th May 2018) - Chen, Hao; Wang, Hao; Li, Biyun; Feng, Bei; He, Xiaomin; Fu, Wei; Yuan, Huihua; Xu, Zhiwei
Abstract : A novel citric acid functionalized chitosan hydrogel for tracheal cartilage regeneration applications. Abstract : Congenital tracheal stenosis in infants and children is a worldwide clinical problem. Tissue engineering is a promising method for correcting long segmental tracheal defects. Nonetheless, the lack of desirable scaffolds always limits the development and applications of tissue engineering in clinical practice. In this study, a citric-acid-functionalized chitosan (CC) hydrogel was fabricated by a freeze–thaw method. Fourier transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD) confirmed that citric acid was successfully attached to the chitosan hydrogel. Scanning electron microscopy (SEM) images and compression tests showed that the CC hydrogel had an interconnected porous structure and better wet mechanical properties. Using morphological and proliferation analyses, cell biocompatibility of the CC hydrogel was shown by culturing human mesenchymal stem cells (hMSCs) on it. Specific expression of cartilage-related markers was analyzed by real-time polymerase chain reaction and western blotting. The expression of chondrocytic markers was strongly upregulated in the culture on the CC hydrogel. Hematoxylin and eosin staining revealed that the cells had the characteristic shape of chondrocytes and clustered into the CC hydrogel. Both Alcian blue staining and a sulfated glycosaminoglycan (sGAG) assay indicated that the CC hydrogel promoted the expression of glycosaminoglycans (GAGs). In a nutshell, these results suggested that the CC hydrogel enhanced chondrogenic differentiation of hMSCs. Thus, the newly developed CC hydrogel may be a promising tissue-engineered scaffold for tracheal cartilage regeneration.